Foucault : a very short introduction - Gutting, Gary (Oxford University Press, 2005)
Foucault is one of those rare philosophers who has become a cult figure. Born in 1926 in France, over the course of his life he dabbled in drugs, politics, and the Paris SM scene, all whilst striving to understand the deep concepts of identity, knowledge, and power.